Water extract of pomegranate ash (WEPA) catalyzed ,green and efficient one pot multicomponent synthesis of 5 -amino pyrazole 4carbonitrile (Indian Journal of Chemistry (IJC), 2024)
In this Work we described one pot multicomponet synthetic approach for 5 aminopyrazole -4 carbonitrile synthesis by using WEPA(Water extract of pomegranate ash) as an organo Catalyst .A series of substituted derivatives of product were synthesized placing this easy and efficient catalyst as green organic solvent .The reaction involes condensation of malononitrile ,benzaldehyde ,and phenylhydrazine generating one pot pyrazole product .The synthetic route of this work involving green solvent and less hazardous reactions. The advantages for this protocol are minimum reaction period ,high percentage of yield, less hazardous and operational simplicity .